2013
DOI: 10.1111/jgh.12261
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metallothionein‐1 and metallothionein‐2 as a prognostic marker in hepatocellular carcinoma

Abstract: The expression of MT-1 and MT-2 may play a role in HCC differentiation and carcinogenesis, and may predict prognosis in patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Later on, the expression of MT1/2 was evaluated immunohistochemically in tissue microarrays containing samples from HCCs, adjacent noncancerous livers, and normal livers [56]. This study demonstrated the loss of nuclear and cytoplasmic expression of MT1/2 in HCC compared with adjacent noncancerous liver tissues and that the loss of nuclear MT1/2 expression is an independent prognostic indicator of poor recurrence-free survival and overall survival in patients with HCC [56].…”
Section: Hepatic Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, the expression of MT1/2 was evaluated immunohistochemically in tissue microarrays containing samples from HCCs, adjacent noncancerous livers, and normal livers [56]. This study demonstrated the loss of nuclear and cytoplasmic expression of MT1/2 in HCC compared with adjacent noncancerous liver tissues and that the loss of nuclear MT1/2 expression is an independent prognostic indicator of poor recurrence-free survival and overall survival in patients with HCC [56].…”
Section: Hepatic Tumoursmentioning
confidence: 99%
“…This study demonstrated the loss of nuclear and cytoplasmic expression of MT1/2 in HCC compared with adjacent noncancerous liver tissues and that the loss of nuclear MT1/2 expression is an independent prognostic indicator of poor recurrence-free survival and overall survival in patients with HCC [56].…”
Section: Hepatic Tumoursmentioning
confidence: 99%
“…31 In fact, human HCC tumor cells show significantly higher loss of nuclear and cytoplasmic MT expression than in noncancerous livers and MT expression loss may be related to poorer overall survival prognosis. 32 Patients with Wilson's disease and HCC from the published literature were recently collated: 86% were male, mean age was 42 years (range 12-73 years), and all were cirrhotic except one. 33,34 Further analysis of the clinical details from those 28 patients revealed that a hepatic copper quantification was determined in 16 patients and was above the normal range in 14 of 16 patients (88%).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to many other cancers, in HCC tissues, MT-1 and MT-2 expression, evaluated by microarray, has been found to be reduced, a fact correlated with a poor prognosis [39] . Additionally, reduced expression levels have been correlated to higher HCC grade and tumor vascular invasion [40] . Together these data indicate that the down-regulation of MT-1 and MT-2 may be undertaken as a poor prognostic factor for HCC patients.…”
Section: Metallothioneinsmentioning
confidence: 99%